2013
DOI: 10.5185/amlett.2013.icnano.108
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis And Characterization Of Silver Nanoparticles embedded In Polyaniline Nanocomposite 

Abstract: Conducting polyaniline/silver nanoparticles (PANI-Ag) nanocomposite was synthesized by in-situ polymerization of aniline in the presence of silver nitrate as precursor. Nanocomposite was characterized by UV-VIS, PL, XRD, FTIR, SEM and TGA to study the effect of silver nanoparticles embedded into PANI on the morphology, structure, crystalline and thermal stability of the conducting polyaniline. The optical studies show that the absorption edge of PANI-Ag nanocomposite exhibits the significant blue shift. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 7 publications
6
36
0
Order By: Relevance
“…However, in some studies a fair agreement has been reported among the experimental and theoretical values. For example, Thakur et al [33] have reported swelling behaviors of chitosan/xanthan gum blended hydrogels and found an excellent agreement for chitosan/xanthan gum hydrogels of varying compositions. The regression values obtained in the present work for second order model are in the range of 0.9700-0.9965, thus proving the fitness of this model.…”
Section: Modeling Of Dynamic Water Uptake Datamentioning
confidence: 93%
See 1 more Smart Citation
“…However, in some studies a fair agreement has been reported among the experimental and theoretical values. For example, Thakur et al [33] have reported swelling behaviors of chitosan/xanthan gum blended hydrogels and found an excellent agreement for chitosan/xanthan gum hydrogels of varying compositions. The regression values obtained in the present work for second order model are in the range of 0.9700-0.9965, thus proving the fitness of this model.…”
Section: Modeling Of Dynamic Water Uptake Datamentioning
confidence: 93%
“…However, the X-ray diffraction pattern of sample Ag NPs/HG1 exhibits strong peaks at 38.12 • , 44.28 • and 66.46 • which are attributed to the Brags reflections at (1 1 1), (2 0 0) and (2 2 0) planes of face centered cubic (FCC) crystals of silver nanoparticles [32,33]. The TG analysis profiles for plain sample HG1 and Ag NPs/HG1 composite hydrogel are shown in Fig.…”
Section: Characterization Of Semi-ipn and Its Silver Nanocompositementioning
confidence: 99%
“…The polymerization of aniline (An) in the presence of Ag + ions gave poly(An)/SN nanocomposites with electrical conductance subject to controlled variation as well as UV-absorbing and photoluminescent properties [129]. The use of substituted anilines as comonomers improves the heat stability of the nanocomposites but decreases their conductivity [130].…”
Section: Hybrid Systems With An Organic Polymer Matrixmentioning
confidence: 99%
“…Among these devices considerable attention is given to the fabrication and characterization of Schottky diodes using polymer and metals because Schottky diode offer several advantages over other diodes such as low forward voltage drop, less heat, high efficiency, high current density and low capacitance [1][2][3][4].Among all conducting polymers, polyaniline (PANI) and its derivatives are more attracted because of its chemical stability, simple preparation, high conductivity and low cost [5][6][7]. Bulk silver shows the highest electrical conductivity among metals at room temperature and it is an adept for producing conducting composites [8,9]. Schottky diode preparation using PANI/Ag is another important subject and have great technological importance for wide variety of applications such as Photovoltaic systems, power supply, RF detector etc.…”
Section: Introductionmentioning
confidence: 99%